Cardiovascular complications of multiple myeloma in the elderly. (2nd December 2017) - Mathur, Pankaj; Thanendrarajan, Sharmilan; Paydak, Hakan; Vallurupalli, Srikanth; Jambhekar, Kedar; Bhatti, Sabha; Schinke, Carolina D; Davies, Faith E; Mehta, Jawahar L
ABSTRACT: Introduction : Multiple myeloma is a malignant neoplasm characterized by plasma cell proliferation in blood and bone marrow. Approximately two-thirds of the patients with multiple myeloma are >65 years at the time of diagnosis. Patients in this age group often have co-existing cardiovascular diseases. Areas covered : The presence of multiple myeloma adds to the malady by direct deposition of amyloid protein in the heart or via toxicity of chemotherapeutic agents. Cardiac contractile dysfunction, arrhythmias and thromboembolic disorders are the main issues in the management of elderly patients with multiple myeloma. Expert commentary : Assessment of cardiac risk and functional status requires careful evaluation by history, physical examination and imaging studies such as echocardiography and magnetic resonance imaging. The management of cardiovascular disorders in the presence of multiple myeloma is difficult and poses a challenge for the internist, the oncologist, and the cardiologist alike. This review is an overview of the problem of cardiovascular risk in and management of elderly patients with multiple myeloma.